PENGARUH BEBAN KERJA DAN STRESS KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PEKERJAAN UMUM KABUPATEN MAJENE - wahdaniah wahdaniah; Andi Gunardi (Universitas Sulawesi Barat, 2018)
This study aims to determine the effect of workload and work stress both partially and simultaneously on the performance of employees at the Public Works Department of Majene Regency. This study is a research using the number of respondents as many as 66 employees. Instruments in this study have passed the test phase of validity and reliability test. Data were collected using questionnaire, while data analysis was done by using multiple linear regression analysis. Result of research at 5% significance level indicate that, work load of employee at Office of Public Works of Kabuapten Majene have influence to employees and job stress at Office of Public Works of Regency of Majene have influence to employee performance and work load and work stress simultant influence to employee performance.